The effects of vitamin B and D supplementations on autonomic functions and quality of life in children after vasovagal syncope - Kovalchuk, Tetiana; Boyarchuk, Oksana; Balatska, Nataliya (Frontiers in Pediatrics, 2025)
Aim of the studyThe aim of the study was to assess the effectiveness of vitamin B6, B9, B12, and D3 supplements in reducing symptoms and the frequency of syncope, improving autonomic nervous system functions, and enhancing quality of life (QOL) in children following an episode of vasovagal syncope (VVS).Materials and methodsThe study involved 68 adolescents with VVS who consistently took vitamin B and D supplements and returned for the examination after 3 months. The effectiveness of the therapy was assessed using the CSSS (Calgary Syncope Seizure Score) and MCSSS (Modified Calgary Syncope Seizure Score), serum vitamin profiles (measured using the ELISA method), heart rate variability, blood pressure variability, and the PedsQL™ (Pediatric Quality of Life Inventory™) 4.0 Generic Core Scales and PedsQL™ 2.0 Family Impact Module surveys.ResultsThe study demonstrated that 3 months of vitamin supplementation were associated with a significant reduction in the frequency of symptoms and syncope episodes (p < 0.05). A marked decrease in serum homocysteine levels was observed, from 13.8 (9.9–17.9) µmol/L to 8.5 (7.6–10.8) µmol/L (p < 0.001). Vitamin supplementation also resulted in improved heart rate variability, evidenced by a significant increase in the SDANN index (p = 0.03) and reductions in TP (p = 0.002), LF (p = 0.004), and LF/HF (p = 0.01), indicating a decrease in sympathotonic influences on the cardiovascular system. Additionally, improved cardiac autonomic function in children with VVS during therapy was reflected by a higher prevalence of dipper profiles for systolic (p = 0.008) and diastolic (p < 0.001) blood pressure. During the 3-month therapy, the QOL in children showed improvements in physical, emotional, and school functioning (p < 0.05). In parents of children with a history of VVS, there were enhancements in physical, emotional, social, and cognitive functioning, as well as in communication and a reduction in worry levels. Among family members, daily activities and family relationships also improved (p < 0.05).ConclusionThe use of vitamin B6, B9, B12, and D3 supplements in therapeutic and preventive doses over 3 months in patients with a history of VVS is associated with a reduction in symptoms and syncope frequency, a decrease in serum homocysteine levels, a reduction in autonomic dysregulation, and an improvement in the QOL for children and their families.